Creative strategy : reconnecting business and innovation - Bilton, Chris; Cummings, Stephen (Chichester, U.K. : John Wiley & Sons, 2010)
Annotation Argues that the divide between'creative' and'other' organizations or industries is a misconception that actually diminishes creative potential in both of these domains. This book promotes an interconnected four stage process, outlining: the six degrees of strategic innovation.
When strategy meets creativity -- False separations and creative connections -- What is creativity? -- Uncreative strategy -- A more creative view of strategy -- Creating and discovering a creative strategy process -- I: The innovative act: discovery and creation -- The bisociations of strategic innovation -- The six outcomes of strategic innovation -- Sparking strategic innovation -- II: Strategic entrepreneurship: dilettantes and diligence -- The five angles of strategic entrepreneurship -- Three angular journeys of entrepreneurship -- III: Strategic leadership: envisioning and interacting -- Leading from the middle -- The strategic leadership keypad -- Shifting keys: leadership as envisioning and interacting -- IV: Strategic organization: focusing and loosening -- From principles of excellent organizations to organizational'virtues' -- Seven virtues of strategic organization -- Strategic organization: where creative strategy ends (and begins again).
Title from title screen.
Includes bibliographical references.
Keywords: Strategic planning; Creative ability in business; Technological innovations; Creative ability in business; Strategic planning; Technological innovations; Electronic books